Reconceptualizing the Role of Educational Leaders through the Integration of Digital Transformation and Spiritual Leadership from the Perspective of Islamic Educational Management - Mohamad Hisyam Syafa'at; Siti Aimah (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to develop a conceptual framework regarding the role of educational leaders who are capable of integrating digital capabilities with spiritual leadership from the perspective of Islamic Educational Management. This study employs a qualitative approach using a case study design at Madrasah Aliyah Raudhatut Tholabah Setail Genteng in Banyuwangi to examine the integration of digital transformation and spiritual leadership in Islamic educational leadership. The research was conducted over one month, involving six non-participatory observations, and included four informants—the madrasah principal, the vice principal for curriculum, a senior teacher, and an administrative staff member—through semi-structured interviews and documentation. Data analysis was conducted interactively through condensation, presentation, and drawing of conclusions using a phased coding technique and triangulation to ensure data validity. The results indicate that educational leadership at Madrasah Aliyah Raudhatut Tholabah has evolved into an integrative model that combines digital transformation with spiritual values within Islamic Educational Management. This shift does not alter the substance of leadership duties but expands managerial practices through the use of technology that remains grounded in ethics, responsibility, and the public good. Technology serves not only as a tool for efficiency but also as a means of strengthening transparency, accountability, and the quality of educational services. These findings affirm that modernization need not lead to technical dominance but can instead reinforce moral and spiritual values. This study contributes to highlighting the importance of integrating digital competencies and values in leadership and demonstrates that madrasahs serve as models for harmonizing technology and religious character. Further research is recommended to test this model in a broader range of Islamic educational institutions using more measurable indicators.